The Recombinant Human Erythropoietin Administered in Neonatal Rats After Excitotoxic Damage Induces Molecular Changes in the Hippocampus - Rivera-Cervantes, Martha Catalina; Jarero-Basulto, José Jaime; Murguía-Castillo, Justo; Marín-López, Alejandra Guadalupe; Gasca-Martínez, Yadira; Cornelio-Martínez, Sergio; Beas-Zárate, Carlos (Frontiers in Neuroscience, 2019)
In vitro and in vivo experimental evidence has contributed important knowledge regarding the antiapoptotic effect mediated by EPO signaling in the damaged brain, particularly through different models with a hypoxic component. However, little emphasis has been placed on the effectiveness of rhEPO administration against cellular alterations caused by in vivo excitotoxicity or on the molecular mechanism that regulates this effect. In this study, we investigated the effects of a single dose of rhEPO on hippocampal damage induced by subcutaneous application of monosodium glutamate (MSG) on postnatal days 1, 3, 5 and 7 in neonatal rats. We found that a dose of 1000 IU/kg of b.w. administered 24 h after MSG had the greatest protective effect. In addition, we analyzed changes in gene expression, particularly in 3 key molecules involved in EPO-mediated signaling (EPO, EPOR and βcR). We observed that the expression of EPO and EPOR was differentially modified at both the mRNA and protein levels under the evaluated conditions, while the expression of the βcR gene was substantially increased. Our data suggest that a low dose of rhEPO is sufficient to induce cellular protection under these experimental conditions and that the molecular changes could be a positive feedback mechanism, mediated by reactive astrocytes in association with in vivo neuroprotective mechanisms.